Gestão de resíduos sólidos urbanos: contribuições socioambientais de duas cooperativas de catadores de materiais recicláveis na região do Médio Paranapanema - Campos, Vanessa Escobar [UNESP] (2014)
The Law approval No. 12.305/10 which stablishes the National Solid Waste (PNRS) provides general guidelines and guides properly the States and Municipalities on the management of solid waste, including, finally, solid waste management in the priority strategies for the country sustainable development. Even though garbage recycling is a registered activity for centuries in Brazil, reducing environmental impacts and generating income for workers, deploy an integrated solid waste management system to the selective collection implementation performed by recyclable materials collectors encounter various political, economic, social and environmental barriers. In this context, initiatives are being developed and overcoming these obstacles, encompassing the collector's appreciation and partnerships settlements to an organized civil society and public institutions. Through systematization experiences, secondary data analysis that were available in publications and technical journals, and primary data obtained from the recyclable materials collectors enterprise from Assis and Ourinhos, which we were attempted to analyze political, economic, social and environmental benefits obtained from the implementation of a social system for the recycling of wastes. The results suggest that recycling administered through solidarity enterprises that promotes maximization of social rather than profit returns may be considered a source of socio-economic inclusion and an efficient process for reducing the volume of solid waste intended to landfills. Moreover, it engage the conscious participation of the population, environment conservation and compliance with environmental standards however hold new practices and concepts, which involves sustainable and solidary development are required by the whole society.